A study on physiological characteristics of elite and sub-elite male badminton players of Delhi region - Gahlot, P. (International Research Journal of Management Sociology & Humanity, 2016)
Aside from the technical, tactical, and training aspects of modern competitive badminton, the physical demands are continually changing, with players in action demonstrating intense rhythmic movement, this combination of physical movement skills raises the question of what physical and physiological attributes of elite badminton players sets them apart from sub-elite players. For the purpose of the study 60 (30 Elite+ 30 Sub-Elite) Male Badminton players were selected from the Delhi region to act as subject for the study. Further Elite players were having minimum Nationals level participation, whereas Sub-Elite players were having minimum State level participation in the respective sport. The age of the subjects ranged between 18 to 25 years, the physical and physiological fitness of these players were tested at Yamuna Vihar Sports Complex, Sri-fort Sports Complex and Dwarka Sports Complex. The players were informed of the possible risks and discomfort related to the battery of physical performance tests before written informed consent was obtained before testing began. The subjects were tested for Body Mass, Standing Height, Body Mass Index, Body Fat, Lean Body Mass, Vo2 Max, and Blood Pressure. The collected data was analyzed by computing Descriptive Statistics and Independent Sample`t` test, results indicates that the descriptive analysis of the Elite level badminton players for Body Mass, Standing Height, Body Mass Index, Body Fat, Lean Body Mass, Vo2 Max, Systolic Blood pressure and Diastolic Blood Pressure are found to be 69.8±6.7, 1.75±0.02, 24.2±1.97, 13.2±3.4, 60.6±6.2, 54.8±3.2 128±12.2 and 82±8.8 respectively, that of and sub Elite are found to be 66.8±6.2, 1.71±0.04, 21.2±1.84, 11.1±2.7, 56.6.±5.6, 51.8±2.9 136±12.8 and 88±8.2 respectively, A significant difference has been found in all the selected Physical and Physiological variables between Elite and Sub-Elite Badminton players of Delhi Region.